Efficient Three Party Key Exchange Protocol - H. K. Pathak; Manju Sanghi (Institute of Advanced Engineering and Science, 2012)
Key exchange protocols allow two or more parties communicating over a public network to establish a common secret key called a session key. In 1976, Diffie and Hellman proposed the first practical key exchange (DH key exchange) protocol. In 2005, Abdalla and Pointcheval suggested a new variation of the computational DH assumption called chosen based computational Diffie Hellman (CCDH) and presented simple password based authenticated key exchange protocols. Since then several three party password authenticated key agreement protocols have been proposed In 2007, Lu and Cao proposed a simple 3 party authenticated key exchange (S-3PAKE) protocol. Kim and Koi found that this protocol cannot resist undetectable online password guessing attack and gave fixed STPKE’ protocol as a countermeasure using exclusive-or operation. Recently, Tallapally and Padmavathy found that STPKE’ is still vulnerable to undetectable online password guessing attack and gave a modified STPKE’ protocol. Unfortunately, we find that, although modified STPKE’ protocol can resist undetectable online password guessing attack but it is vulnerable to man in the middle attack. Also, we propose and analyze an efficient protocol against all the known attacks.